Long-term efficacy of interferon-alpha and ursodeoxycholic acid in treatment of chronic type C hepatitis - (:unkn) unknown (SPRINGER, 1997)
Interferon-alpha (IFN) and ursodeoxycholic acid (UDCA) combined have a controversial role in the treatment of chronic type C hepatitis. We studied the long-term efficacy of both drugs alone or in combination. In a three-year period, 108 patients were randomized into three treatment arms: (1) IFN alone 3 MU three times a week (N = 49), (2) IFN 3 MU three times a week + UDCA 250 mg twice a day (N = 45), and (3) UDCA alone 250 mg twice a day (N 14). Response was defined as complete normalization of serum ALT. For the responders at the end of six months, the treatment was run to 12 months. Nonresponders (NRs) of the first group were crossed over to combination and NRs of the combination received 6 MU three times a week IFN + UDCA for the next six months. The enrollment to the UDCA alone arm was stopped early, since only 1/14 normalized serum ALT at the end of third month. However, 12/14 completed six months and 11 NRs received IFN 3 MU three times a week alone for the next six months. Twelve discontinued treatment due to side effects. Responders were followed-up untreated for 18 months. Sustained response (SR) was defined as persistence of normal serum ALT levels in this period. At the end of six months, 22/45 (48%) from the IFN-alone and 23/39 (58%) from the combination group responded. Twenty NRs from former and 15 of latter group were crossed over. While none of the 20 from the IFN-alone group responded to the combination, 1/15 NRs of the combination group responded to dose escalation. SR was achieved in 9/45 (20%) of the IFN alone and 7/39 (18%) of the combination group. The mean time form the end of the treatment to the relapse was not different between the groups. Five of 11 UDCA NRs responded to IFN with SR in 2. It was concluded that UDCA as a single agent is ineffective in achieving response in the treatment of chronic type C hepatitis. Combined with IFN, it increases response rate insignificantly although this is not sustained.
Keywords: hepatitis C; interferon-alpha; ursodeoxycholic acid; NON-B-HEPATITIS; POLYMERASE CHAIN-REACTION; PLACEBO-CONTROLLED TRIAL; CHRONIC NON-A; DOUBLE-BLIND; RANDOMIZED TRIAL; LIVER-DISEASE; ALFA THERAPY; BLOOD-DONORS; BILE-SALTS